2023
DOI: 10.3390/cancers15082230
|View full text |Cite
|
Sign up to set email alerts
|

Perinucleolar Compartment (PNC) Prevalence as an Independent Prognostic Factor in Pediatric Ewing Sarcoma: A Multi-Institutional Study

Abstract: The perinucleolar compartment (PNC) is a small nuclear body that plays important role in tumorigenesis. PNC prevalence correlates with poor prognosis and cancer metastasis. Its expression in pediatric Ewing sarcoma (EWS) has not previously been documented. In this study, we analyzed 40 EWS tumor cases from Caucasian and Hispanic patients for PNC prevalence by immunohistochemical detection of polypyrimidine tract binding protein and correlated the prevalence with dysregulated microRNA profiles. EWS cases showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The original identification of RAVER1 revealed its association and co-localization with PTBPs in perinucleolar compartments ( Supplementary Figure S3A ) ( 17 ). Independent studies suggested elevated frequency of PNCs in progressed, metastatic malignancies ( 22 , 23 ). Accordingly, it was tempting to speculate that RAVER1’s role in tumor cell proliferation is associated with its potentially PTBP-dependent modulation of PNC homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original identification of RAVER1 revealed its association and co-localization with PTBPs in perinucleolar compartments ( Supplementary Figure S3A ) ( 17 ). Independent studies suggested elevated frequency of PNCs in progressed, metastatic malignancies ( 22 , 23 ). Accordingly, it was tempting to speculate that RAVER1’s role in tumor cell proliferation is associated with its potentially PTBP-dependent modulation of PNC homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…In s.c. LUAD (A549) xenograft mouse models, the loss of RAVER1 even reduced tumor growth, indicating that RAVER1 serves a rather pro-oncogenic role in lung and presumably other cancers. PTBPs and RAVER1 associate and co-localize in perinucleolar compartments (PNCs, ( 17 )), which were proposed to be enhanced in progressed malignancies ( 22 , 23 ). Thus, it was tempting to speculate that RAVER1 modulates tumor cell fate in a PNC-dependent manner.…”
Section: Discussionmentioning
confidence: 99%